Biology gateways DNA, RNA, and proteins (Cambridge : Logal Software, 1998)
Logal's science gateways series provides introductory level biology and chemistry students with easy-to-use software that increases understanding of key concepts and ideas
System requirements: 486 or higher, Windows 95/98 or NT, 16 MB RAM, QuickTime 32-bit, sound capabilities, CD-ROM
Keywords: DNA; RNA; Proteins